Implementasi Sekolah Adiwiyata Terhadap Pembentukan Karakter Kedisiplinan dan Entrepreneurship Siswa di MI Salafiyah Tanjung - Anis Rochmawati Barokah; Rahmat Kamal (Madako Elementary School, 2023)
To produce quality learning, a good school environment is essential. This environment plays a role in building student character, building discipline and entrepreneurship spirit through the adiwiyata school program.  The goal of the adiwiyata school program is to shape students' entrepreneurial characteristics through the program. This qualitative research uses a descriptive approach to investigate the various ways the adiwiyata school program shapes students' disciplinary and entrepreneurial characters.  The results of this study can help the adiwiyata school program improve the quality of students' disciplinary character. Overall, the results of this study are expected to increase and improve student discipline in adiwiyata-based madrasah ibtidaiyah while fostering the value of students' entrepreneurial spirit.